Andrey Zvyagintsev’s Loveless as the remediation of Mikhail Bulgakov’s The heart of a dog. Towards the question of cultural memory - Waligórska-Olejniczak , Beata (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article aims to examine the relationship between two texts: Loveless (Нелюбовь, 2017), the latest of Andrey Zvyagintsev’s feature films, and The Heart of a Dog (Собачье сердце, 1925), one of Mikhail Bulgakov’s most popular short stories. The studies are focused on finding the parallels showing the work of cultural memory, which is understood – following Aleida Assmann’s and Astrid Erll’s findings – as the process of continuous remediation, retranscription and negotiation of essential ideas in the space of culture. Consequently, the author is not interested in treating Zvyagintsev’s text as the illustration of Bulgakov’s plot, but rather in discussing certain topics which are deposited in Russian literature and constantly reused and reinterpreted, creating the framework for communication across ‘the abyss of time’. The analogies between the selected texts are sought in the area of their structure, some thematic overlapping, the authors’ approach to the issue of the authoritarian ideology and the role of technology as well as in exploring the function of space as one of the narrative mechanisms, in particular in the context of the category of home and anti-home.